Rola państwa we współczesnej gospodarce rynkowej - Dobrzański, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The main goal of the article is to present the contemporary role of government in market economy. In the first part of the article ahistorical view on the role of government has been presented. In addition, the article discusses instruments used by the government to affect economic processes. Moreover, the author emphasizes the issue of government efficiency. Finally, the article presents contemporary conditions of state activities related to the process of globalization and integration. The main research method applied is acritical analysis of Polish and foreign literature.
Keywords: państwo; gospodarka rynkowa; ujęcie historyczne; efektywność; globalizacja; integracja